Immersion in 6-Benzylaminopurine for Dormancy Release and Initiation of Potato Sprouts at Various Tuber Weight and Storage Duration - Siregar, Luthfi Aziz Mahmud; Lambok Turnip; I.M. Revandi Damanik (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2021)
One of the main obstacles in providing quality potato seed tubers is the long dormancy period of the potato seeds. A study that explores this has been carried out to elucidate the response of dormancy release and initiation of potato sprouts to the differences in tuber weight and storage duration before immersion in cytokinin (6-benzylaminopurine). The study was conducted at the seed warehouse UPT Horticulture Parent Seed Kutagadung Berastagi, Department of Food and Horticulture of North Sumatra Province, from November 2018 to January 2019. The research was carried out with a factorial completely randomized design with two factors, namely (i) tuber weight, consisting of 4 levels [25-35 g, 55-65 g, 85-95g, and 115-125 g]; and (ii) tuber storage duration before immersion in 6-benzylaminopurine (BAP) solution, consisting of 5 levels [control (without immersion), 1, 15, 30, and 45 days after harvest]. Tuber weight, storage duration before immersion, and the interaction of the two factors showed significant effects in dormancy breaking time, germination percentage, germination rate, number of sprouts, and length of sprouts. The number and length of the sprouts increased with the increasing tuber weight and storage duration before immersion in BAP. Keywords: cytokinin, germination, Solanum tuberosum L., tuber seeds